PENERAPAN FUNGSI DASAR MANAJEMEN PENDIDIKAN ISLAM DALAM MANAJEMEN BERBASIS TEKNOLOGI DI PESANTREN MODERN - Yuli Maulana; Mulyawan Safwandi Nugraha (Universitas Islam Negeri Sumatera Utara Medan, 2025)
The digital transformation occurring within Islamic educational institutions requires a more adaptive and professional management system capable of meeting the demands for efficiency, accountability, and quality improvement. This study aims to analyze the implementation of fundamental Islamic educational management functions (POAC: Planning, Organizing, Actuating, Controlling) within a technology-based management system at Al-Ma'soem Islamic Boarding School, as well as to identify the challenges and opportunities emerging from this digitalization process. Employing a qualitative field-study design, data were collected through in-depth interviews, limited observations, and document analysis related to the digital management system. The findings indicate that planning, organizing, actuating, and controlling have been integrated through the use of management information systems, digital-competence-based staff recruitment, the utilization of digital administrative and learning applications, and monitoring mechanisms supported by dashboards and content-filtering systems. The results confirm that digitalization enhances the effectiveness of pesantren governance, although its success depends heavily on human resource readiness, infrastructure stability, and an organizational culture supportive of innovation. Theoretically, this study expands the discourse on Islamic educational management by offering the POAC-Digital concept, which integrates technological adaptation with Islamic values. Practically, the findings provide a strategic reference for developing modern pesantren management models that are more effective, accountable, and quality-oriented.